Lived experiences, challenges, and accommodations in OJT and employment in accounting-related roles: Evidence from DLSU-M PWD accountancy trainees and graduates - Sy-Reyes, Denica C (Animo Repository, 2023)
Persons with disabilities (PWDs) in the Philippines remain vulnerable to marginalization despite promotions of inclusivity and equal treatment, but little research is done on PWD experiences in the accounting workplace. This research aims to determine how DLSU M PWD BSA trainees and graduates assigned in accounting-related roles are treated in the workplace, and identify what accommodations are in place to facilitate workplace integration. It looks at how they are treated, what accommodations are currently made available by HTEs/Employers, what challenges and/or limitations they experience due to their disability, what measures were taken by PWDs to address or mitigate the potential challenges and/or limitations due to their disabilities, and what common support systems, accommodations, and resources are currently available to PWDs in the accounting workplace. An oral history interview was conducted with seven participants, the transcripts analyzed using thematic analysis. The demographics showed that the timing of disability diagnoses is a significant factor. The interviews showed that there is no differential treatment nor discrimination against PWDs. The PWDs themselves are open to creating adjustments to their work environment, and HTEs/Employers either adopt a proactive or responsive stance to accommodations, support systems, and resources. Overall, the challenges and limitations faced are primarily dependent on the type and severity of their disabilities and whether they have an aid but generally, there are no difference in treatment between PWD and non-PWD trainees and graduates, and it is important to disclose disabilities to access appropriate accommodations.